Electric Field Calculation and Comparative Analysis of Conventional and Unconventional Transmission Lines - Easir Arafat; Babak Porkar; Mona Ghassemi (IEEE Access)
As global electricity demand continues to rise, innovative transmission line designs are being developed to enhance efficiency and reliability. Recent studies emphasize the urgent need for advanced structures that improve transmission capabilities. In this context, optimally designed unconventional lines with higher natural power emerge as potential game changers. Various electrical, mechanical, and structural aspects must be studied for a new overhead line design. Among them, evaluating these new transmission line designs against established safety standards is crucial, particularly concerning low-frequency (50 or 60 Hz) electric fields generated under these new lines. This paper comprehensively analyzes the electric fields generated by conventional and unconventional overhead transmission lines. By calculating the electric field for each sub-conductor individually, we offer a detailed comparison highlighting the differences in field distribution between these two line types. Our findings indicate that the unconventional transmission lines exhibit a more favorable electric field profile and comply with current exposure limits set by regulatory agencies. This research underscores the potential of unconventional designs to improve safety and minimize environmental impact while addressing the challenges posed by increasing electricity demands.